Effect of fluid intake on the outcome of constipation in children: PEG 4000 versus lactulose - Bae, Sun Hwan; Son, Jae Sung; Lee, Ran (Pediatrics international, 2010)
Background:  The aim of the present study was to evaluate the effect of fluid intake on the outcome of treatment with osmotic laxatives, PEG 4000 and lactulose, in children with chronic constipation. Methods:  Medical records were reviewed, and 27 children with chronic constipation satisfying the following criteria were enrolled: (i) on stable maintenance medication for ≥3 months; (ii) no dosage modification or drug change between the two periods compared; (iii) no clinical events during the investigation that could affect intake or the clinical outcomes; (iv) good compliance regarding inclusion in the diaries of the frequency of bowel movements, the consistency of stools, and the amount of fluid intake. The diary covered >25 days per visit; and (v) interval of <3 months between the two periods compared. A scoring system was developed for bowel movements and for stool consistency. The score during a period of better fluid intake was compared to that during a period of worse fluid intake, for the same patient. Wilcoxon signed‐rank test was used for the analysis. Results:  On polyethylene glycol 4000 (PEG 4000; n= 14), the bowel movement score on good fluid intake was 21.43–30.00 (median, 27.78), while that on poor fluid intake was 19.00–30.00 (median, 25.13; P= 0.009). For stool consistency, the score on good fluid intake was 11.79–20.00 (median, 20.00), while that on poor fluid intake was 11.00–25.00 (median, 15.91; P= 0.002). On lactulose (n= 13) there was no statistical difference with respect to the two categories of defecation. Conclusions:  Children who are already on PEG 4000 still benefit from additional fluid intake.